Documentation Bulletin No. 14 - Planning Commission (Planning Commission, 1974)
The Village Sanitation or Bhangi Mukti Scheme was one of the four fold activities of the Gandhi Smarak Nidhi (G.S.N.). It aimed at constructing the latrines free from the services of sweepers, providing privacy particularly to the women folk, utilizing night for the production of manure and making the villages generally clean. The latrines popularised by the Gandhi Smarak Nidhi were of two types, one was called Sopa, and the other Naigaon. According to the estimates of the Gandhi Smarak Nidhi the cost of the Sopa type of latrine up to the plinth was estimated at Rs.100/- and that of the Naigaon about Rs. 300/-, The Gandhi Smarak Nidhi was manufacturing and supplying the latrine pots.
Programme Evaluation Organisation Planning Commission Government of India